PATTERNS OF ETHNICITY AND INTEGRATION IN MULTICULTURAL SOCIETIES - Muhtar; Sandra I. Telussa, Rukoyah (Adisam Publisher, 2024)
In a country with a multi-ethnic population like Indonesia, cultural conflict is something that cannot be avoided. Previous government policies that used the concept of assimilation meant that ethnic minority cultures had to merge into Indonesian culture as the dominant culture. As a result, ethnic minority cultures are lost or shackled. The concept of Multicultural Integration is offered as an alternative to reduce inter- ethnic conflict. Ethnicity is often seen as something that is situationally determined and symbolically charged. If, for example, platforms for solidarity are described and understood in structural terms, the result may be shifting ethnic identities on the basis of solidarity and politically called for mobilization on the basis of solidarity. Likewise, pressure, discrimination and racism, independent of gross cultural differences, form the basis for broad social solidarity and mobilization and the construction of a collective identity. The integration found in ethnic cultural wisdom is categorized into normative integration. Normative integration is a social bond that occurs because there is an agreement (consensus) on basic values and norms. The pattern of social relations between ethnic groups described above shows that an associative or positive pattern has been formed.